Silicon carbide nanowire based on electrolytic manganese residues as well as preparation method and application of silicon carbide nanowire

By in-situ synthesizing silicon carbide nanowires on an electrolytic manganese slag matrix, optimizing impedance matching and dielectric loss, the problem of insufficient absorption performance of silicon carbide nanowire composites in the low-frequency band was solved, and efficient electromagnetic wave absorption and solid waste resource utilization were achieved.

CN120698804APending Publication Date: 2025-09-26CHANGSHA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510849137.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing silicon carbide nanowire composite materials have difficulty achieving effective impedance matching in the low-frequency band due to insufficient dielectric constant, and the wave-transparent matrix such as paraffin leads to insufficient connectivity of the nanowire network, affecting the electromagnetic wave absorption performance.

Method used

Using electrolytic manganese slag as the matrix, by mixing carbon source, silicon source, pore-forming agent, nickel source and dispersion medium, pressing and sintering, porous silicon carbide nanowires are prepared to optimize impedance matching and dielectric loss and enhance electromagnetic wave absorption performance.

Benefits of technology

It achieves thin thickness, strong absorption and wide frequency band electromagnetic wave absorption performance, and realizes the resource utilization of solid waste, and is suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120698804A_ABST
    Figure CN120698804A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic adsorption materials, in particular to a silicon carbide nanowire based on electrolytic manganese residues and a preparation method and application of the silicon carbide nanowire. The invention provides a preparation method of a silicon carbide nanowire based on electrolytic manganese residue, which comprises the following steps: mixing a carbon source, a silicon source, a pore forming agent, electrolytic manganese residue, a nickel source and a dispersion medium to obtain a mixture; the mixture is subjected to compression molding and sintering in sequence, and the silicon carbide nanowire based on the electrolytic manganese residues is obtained, the sintering temperature ranges from 1000 DEG C to 1300 DEG C, and the heat preservation time ranges from 3 h to 6 h. The silicon carbide nanowire based on the electrolytic manganese residues prepared by the preparation method achieves the purpose of solid waste resource utilization under the condition of meeting the requirements of thin thickness, strong absorption and wide frequency band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic adsorption materials, and in particular to a silicon carbide nanowire based on electrolytic manganese slag, and a preparation method and application thereof. Background Art

[0002] With technological advancements and growing societal demands, 5G and future communication technologies are developing rapidly, creating an increasingly urgent need for electromagnetic wave control and management. Against this backdrop, the critical role of absorbing materials in reducing interference, improving signal quality, and expanding coverage is becoming increasingly prominent. In the military, absorbing materials are a key component of stealth technology. As stealth performance improves, research on absorbing materials is also deepening. Consequently, the development of high-performance absorbing materials to address the challenges posed by electromagnetic waves has garnered widespread attention.

[0003] Although traditional ferrite-based absorbing materials have high magnetic permeability characteristics, their defects such as high density and narrow effective bandwidth make it difficult to meet the needs of lightweight broadband absorption. In recent years, silicon carbide nanowires (SiCnws) have shown significant advantages in the field of new absorbing materials due to their unique one-dimensional nanostructure, high temperature resistance and controllable dielectric loss mechanism. However, existing SiCnws composite materials mostly use a wave-transparent matrix such as paraffin. Their dispersed structure leads to insufficient connectivity of the nanowire network, significantly weakening the interface polarization effect and the construction of conductive paths. In particular, in the low-frequency band, it is difficult to achieve effective impedance matching due to insufficient dielectric constant. Summary of the Invention

[0004] In view of this, the present invention aims to provide a silicon carbide nanowire based on electrolytic manganese slag, a preparation method thereof, and its application. The silicon carbide nanowire based on electrolytic manganese slag prepared by the preparation method achieves the goal of solid waste resource utilization while meeting the requirements of thin thickness, strong absorption, and wide frequency band.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing silicon carbide nanowires based on electrolytic manganese slag, comprising the following steps:

[0007] mixing a carbon source, a silicon source, a pore former, electrolytic manganese slag, a nickel source and a dispersion medium to obtain a mixture;

[0008] The mixture is sequentially pressed and sintered to obtain the silicon carbide nanowires based on electrolytic manganese slag;

[0009] The sintering temperature is 1000-1300° C., and the heat preservation time is 3-6 hours.

[0010] Preferably, the mass ratio of the carbon source to the silicon source is (3-8):(5-10).

[0011] Preferably, the carbon source includes one or more of glucose, sucrose and starch;

[0012] The silicon source includes one or more of silicon dioxide, tetraethyl orthosilicate and phenolic resin.

[0013] Preferably, the mass percentage of the pore-forming agent to the total mass of the pore-forming agent and the electrolytic manganese slag is 5 to 15%;

[0014] The ratio of the mass of the carbon source to the total mass of the pore-forming agent and the electrolytic manganese slag is (3-8): (10-50).

[0015] Preferably, the pore-forming agent comprises one or more of bean dregs, rice husks, corn cobs and coffee grounds.

[0016] Preferably, the mass ratio of the carbon source to the nickel source is (3-8): (2-10);

[0017] The nickel source includes one or more of nickel nitrate, nickel sulfate and nickel chloride.

[0018] Preferably, before the compression molding, drying is also included;

[0019] The drying temperature is 60-100°C and the drying time is 6-12 hours;

[0020] The compression molding pressure is 5-20 MPa, and the holding time is 1-5 minutes.

[0021] Preferably, the sintering is carried out in a protective atmosphere;

[0022] The heating rate to the sintering temperature is 1-10°C / min.

[0023] The present invention also provides silicon carbide nanowires based on electrolytic manganese slag prepared by the preparation method described in the above technical solution.

[0024] The present invention also provides the application of the silicon carbide nanowires based on electrolytic manganese slag described in the above technical solution in the field of electromagnetic wave absorption.

[0025] The present invention provides a method for preparing silicon carbide nanowires based on electrolytic manganese slag, comprising the following steps: mixing a carbon source, a silicon source, a pore-forming agent, electrolytic manganese slag, a nickel source, and a dispersion medium to obtain a mixture; sequentially pressing and sintering the mixture to obtain the electrolytic manganese slag-based silicon carbide nanowires; the sintering temperature is 1000-1300°C, and the holding temperature is 3-6 hours. In the present invention, the electrolytic manganese slag is a hazardous solid waste generated during the hydrometallurgical manganese smelting process, and its main element is iron. By in situ synthesizing silicon carbide nanowires on the electrolytic manganese slag substrate, impedance matching is optimized, gross loss and dielectric loss are synergistically reduced, and solid waste resources are utilized. The present invention utilizes a pore-forming agent to introduce a porous structure into the electrolytic manganese slag-based silicon carbide nanowires, demonstrating the unique advantage of structure-performance synergistic optimization. The addition of the pore-forming agent not only enhances the polarization loss of the material but also extends the electromagnetic wave propagation path, thereby enhancing energy dissipation. Furthermore, the preparation method is simple, rapid, and suitable for large-scale production. At the same time, the sintering time will regulate the material properties by affecting the growth perfection of SiC nanowires, the phase crystallinity of electrolytic manganese slag, the degree of pore structure retention and the interface bonding strength. During the sintering process, the carbon source and the silicon source can fully react to generate SiC nanowires and form chemical bonds with the electrolytic manganese slag matrix. The porous structure formed by the carbonization of the pore-forming agent can be stably retained, and the catalytic effect of the nickel source can be fully exerted, so that the material has both appropriate dielectric loss (SiCnw conductive network and porous polarization) and magnetic loss, achieving efficient electromagnetic wave absorption performance; if the sintering time is too short, the SiCnw growth is incomplete, the interface bonding is weak and the pore collapse is serious, resulting in a single loss mechanism, while too long a time may cause SiCnw agglomeration, grain coarsening and excessive densification, weakening the polarization and scattering effects, all of which will reduce the absorption performance. If the sintering time is too long, SiC nanowires (SiCnw) may agglomerate or overgrow due to long-term high temperature exposure, resulting in the destruction of the conductive network structure and a decrease in dielectric loss capacity; at the same time, the porous structure formed by the carbonization of the pore-forming agent may collapse or shrink due to the sintering effect, the porosity will decrease, the scattering and polarization paths of electromagnetic waves inside the material will be shortened, and the energy dissipation efficiency will be reduced; in addition, too long sintering time may also cause excessive reaction of the internal interface of the material, forming a densified structure, destroying impedance matching, and ultimately leading to increased reflection loss, narrowing of the effective absorption bandwidth, and overall deterioration of the absorption performance.When the sintering time is 6 hours, the silicon carbide nanowires based on electrolytic manganese slag obtained have excellent reflection loss (-51.6 dB, f = 11.8 GHz, d = 2.62 mm) and effective absorption bandwidth (2.04 GHz) in the frequency range of 8.2 to 12.4 GHz. At the same time, the sintering temperature also has an important influence on the structure and performance of the silicon carbide nanowires based on electrolytic manganese slag. When the sintering temperature is in the range of 1000 to 1300 ° C, the carbon source and the silicon source can be fully reacted to form SiC nanowires and form a chemical bond with the electrolytic manganese slag matrix. Bonding stabilizes the porous structure formed by the carbonization of the pore-forming agent, allowing the nickel source's catalytic effect to be fully utilized, resulting in the material having both appropriate dielectric loss and magnetic loss, achieving efficient electromagnetic wave absorption performance. When the sintering temperature is too low, the reaction between the carbon source and the silicon source may not be sufficient, resulting in an incomplete structure and imperfect growth of the resulting silicon carbide nanowires, resulting in weak interfacial bonding strength. The porous structure may not be stably retained due to insufficient temperature, and the pores may collapse severely, thereby reducing the polarization loss of the material, shortening the electromagnetic wave propagation path, weakening the energy dissipation capacity, and deteriorating the absorption performance. At the same time, the phase crystallinity of the electrolytic manganese slag is also low, and it cannot fully play its role in the material, which in turn affects the overall performance of the material. If the sintering temperature is too high, it may cause excessive growth and agglomeration of the silicon carbide nanowires, destroying its conductive network structure and reducing the dielectric loss capacity. In addition, high temperature may cause the pores within the material to shrink or collapse excessively, reducing the porosity, further shortening the scattering and polarization path of electromagnetic waves within the material, and reducing energy dissipation efficiency. At the same time, excessively high temperatures can cause excessive reactions at the material's internal interfaces, resulting in a densified structure and disrupting impedance matching. This can lead to increased reflection losses, a narrowing of the effective absorption bandwidth, and overall deterioration of absorption performance. The electrolytic manganese slag-based silicon carbide nanowires prepared by the method described herein achieve the desired thinness, strong absorption, and wide bandwidth requirements, enabling the resourceful utilization of solid waste and promising broad application prospects in the field of electromagnetic wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SEM images and three-dimensional reflection loss (RL) graphs of SiCnw / EMR-1 described in Example 1 at different magnifications are shown;

[0027] Figure 2 The SEM images and three-dimensional reflection loss (RL) graphs of SiCnw / EMR-2 at different magnifications described in Example 2 are shown;

[0028] Figure 3 The SEM images and three-dimensional reflection loss (RL) graphs of SiCnw / EMR-3 at different magnifications described in Example 3 are shown;

[0029] Figure 43D reflection loss (RL) graphs of silicon carbide nanowires based on electrolytic manganese slag described in Examples 4 to 6. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing silicon carbide nanowires based on electrolytic manganese slag, comprising the following steps:

[0031] mixing a carbon source, a silicon source, a pore former, electrolytic manganese slag, a nickel source and a dispersion medium to obtain a mixture;

[0032] The mixture is sequentially pressed and sintered to obtain the silicon carbide nanowires based on electrolytic manganese slag;

[0033] The sintering temperature is 1000-1300° C., and the heat preservation time is 3-6 hours.

[0034] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0035] The invention mixes a carbon source, a silicon source, a pore-forming agent, an electrolytic manganese slag, a nickel source and a dispersion medium to obtain a mixture.

[0036] In the present invention, the mass ratio of the carbon source to the silicon source is preferably (3-8): (5-10), more preferably 3:5, 3:6, 3:7, 3:8, 3:9, 3:10, 4:5, 4:6, 4:7, 4:9, 4:10, 5:5, 5:6, 5:7, 5:8, 5:9, 6:5, 6:6, 6:7, 6:8, 6:9, 7:5, 7:6, 7:7, 7:8, 7:9, 7:10, 8:5, 8:6, 8:7, 8:8, 8:9 or 8:10. In an embodiment of the present invention, the mass ratio of the carbon source to the silicon source can be 8:5.

[0037] In the present invention, the carbon source preferably includes one or more of glucose, sucrose and starch. When the carbon source is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the carbon source is specifically glucose.

[0038] In the present invention, the silicon source preferably includes one or more of silicon dioxide, tetraethyl orthosilicate, and phenolic resin. When the silicon source includes two or more of the above-mentioned specific selections, the present invention does not have any particular restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the silicon source can be tetraethyl orthosilicate.

[0039] In the present invention, the mass percentage of the pore-forming agent to the total mass of the pore-forming agent and the electrolytic manganese slag is preferably 5-15%, more preferably 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. In an embodiment of the present invention, the mass percentage of the pore-forming agent to the total mass of the pore-forming agent and the electrolytic manganese slag can be 10%.

[0040] In the present invention, the ratio of the mass of the carbon source to the total mass of the pore-forming agent and the electrolytic manganese slag is preferably (3-8): (10-50), more preferably 3:10, 3:20, 3:30, 3:40, 3:50, 4:10, 4:20, 4:30, 4:50, 5:10, 5:20, 5:30, 5:40, 6:10, 6:30, 6:40, 6:50, 7:10, 7:20, 7:30, 7:40, 7:50, 8:10, 8:20, 8:30, 8:40 or 8:50. In an embodiment of the present invention, the ratio of the mass of the carbon source to the total mass of the pore-forming agent and the electrolytic manganese slag can be 8:10.

[0041] In the present invention, the pore-forming agent preferably includes one or more of bean dregs, rice husks, corn cobs, and coffee grounds. When the pore-forming agent comprises two or more of the aforementioned specific materials, the present invention does not impose any particular restrictions on the ratio of the aforementioned specific materials; they may be mixed in any ratio. In an embodiment of the present invention, the pore-forming agent may be bean dregs.

[0042] In the present invention, the mass ratio of the carbon source to the nickel source is preferably (3-8): (2-10), more preferably 3:2, 3:4, 3:6, 3:8, 3:10, 4:2, 4:4, 4:6, 4:8, 4:10, 5:2, 5:4, 5:6, 5:8, 6:2, 6:10, 7:2, 7:4, 7:6, 7:8, 7:10, 8:2, 8:6 or 8:10. In an embodiment of the present invention, the mass ratio of the carbon source to the nickel source can be 8:2.

[0043] In the present invention, the nickel source preferably includes one or more of nickel nitrate, nickel sulfate, and nickel chloride. When the nickel source is two or more of the above-mentioned specific selections, the present invention does not have any particular restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the nickel source can be nickel nitrate.

[0044] In the present invention, the amount ratio of the carbon source to the dispersion medium is preferably (3-8) g: (100-200) mL, more preferably 3 g: 100 mL, 3 g: 150 mL, 3 g: 200 mL, 4 g: 100 mL, 4 g: 150 mL, 4 g: 200 mL, 5 g: 100 mL, 5 g: 150 mL, 5 g: 200 mL, 6 g: 100 mL, 6 g: 150 mL, 7 g: 100 mL, 7 g: 150 mL, 7 g: 200 mL, 8 g: 100 mL or 8 g: 150 mL. In an embodiment of the present invention, the amount ratio of the carbon source to the dispersion medium can be 8 g: 200 mL.

[0045] In the present invention, the dispersion medium preferably includes anhydrous ethanol and water, and the volume ratio of the alcohol to water is preferably (100-300):(100-300), more preferably (150-250):(100-250). In an embodiment of the present invention, the volume ratio of the alcohol to water can be 1:1.

[0046] In the present invention, the mixing preferably includes: a first mixing of a pore-forming agent and electrolytic manganese slag to obtain electrolytic manganese slag containing a pore-forming agent; and a second mixing of a carbon source, a silicon source, electrolytic manganese containing a pore-forming agent, a nickel source, and a dispersion medium. The present invention does not have any special restrictions on the process of the first mixing, and a process well known to those skilled in the art can be used. In the present invention, the second mixing is preferably carried out under stirring conditions, and the stirring speed is preferably 200 to 500 rpm, more preferably 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, or 500 rpm; the stirring time is preferably 2 to 10 hours, more preferably 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. In an embodiment of the present invention, the stirring speed can be 300 rpm and the stirring time can be 6 hours.

[0047] After obtaining the mixture, the present invention sequentially performs compression molding and sintering on the mixture to obtain the electrolytic manganese slag-based silicon carbide nanowires.

[0048] In the present invention, the pressing step preferably includes drying before the pressing step. The drying temperature is preferably 60-100°C, more preferably 60°C, 70°C, 80°C, 90°C, or 100°C; and the drying time is preferably 6-12 hours, more preferably 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours. In an embodiment of the present invention, the drying method may be oven drying, and the drying temperature may be 80°C, and the drying time may be 12 hours.

[0049] In the present invention, the pressure of the press molding is preferably 5-20 MPa, more preferably 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, 16 MPa, 17 MPa, 18 MPa, 19 MPa or 20 MPa; the holding time is preferably 1-5 min, more preferably 1 min, 2 min, 3 min, 4 min or 5 min. In an embodiment of the present invention, the pressure of the press molding can be 10 MPa and the holding time can be 2 min.

[0050] In the present invention, the sintering is preferably carried out in a protective atmosphere, which is preferably a nitrogen atmosphere, an argon atmosphere or a helium atmosphere. In an embodiment of the present invention, the protective atmosphere may be an argon atmosphere.

[0051] In the present invention, the sintering temperature is preferably 1000-1300°C, more preferably 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C; the holding time is 3-6h, preferably 3h, 3.5h, 4h, 4.5h, 5h or 6h; the heating rate to the sintering temperature is preferably 1-10°C / min, more preferably 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min. In an embodiment of the present invention, the sintering temperature can be 1200°C, the holding time can be 3h or 4.5h; the heating rate to the sintering temperature can be 5°C / min.

[0052] After the sintering is completed, the present invention also preferably includes cooling and sealed storage carried out in sequence. In the present invention, the cooling rate of the cooling is preferably 1 to 10°C / min, more preferably 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min. In an embodiment of the present invention, the cooling rate of the cooling may be 5°C / min. In the present invention, the target temperature of the cooling is preferably room temperature. The present invention does not have any special limitation on the process of sealed storage, and the process well known to those skilled in the art may be used.

[0053] The present invention also provides silicon carbide nanowires based on electrolytic manganese slag prepared by the preparation method described in the above technical solution.

[0054] The present invention also provides the application of the silicon carbide nanowires based on electrolytic manganese slag described in the above technical solution in the field of electromagnetic wave absorption. The present invention does not have any special restrictions on the method of the application, and the method well known to those skilled in the art can be used.

[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0056] Example 1

[0057] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0058] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0059] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 3 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-1);

[0060] Figure 1 The SEM images ((a) to (c)) and three-dimensional reflection loss (RL) images ((d)) of the SiCnw / EMR-1 at different magnifications show that the number of silicon carbide nanowires is small and sparsely distributed when grown at a temperature of 3 hours. In the low-magnification image (a), the nanowires are dispersed on the substrate and are relatively far apart. The high-magnification images (b) and (c) show that the nanowire morphology at this time is less regular, with obvious differences in thickness, and the surface of some nanowires is rough; the RL image shows that the SiCnw / EMR-1 only obtains a RL of -13.3dB in the 4.74mm and 8.326GHz frequency bands. min and EAB at 0.11GHz.

[0061] Example 2

[0062] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0063] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0064] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 4.5 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-2);

[0065] Figure 2 The SEM images ((a) to (c)) and three-dimensional reflection loss (RL) images ((d)) of the SiCnw / EMR-2 at different magnifications show that the number of nanowires increases significantly and the distribution becomes denser when the temperature is kept at 4.5h. The number of nanowires intertwined with each other increases, and a more complex structure begins to form. The uniformity of the thickness of the nanowires improves, and the surface is relatively smooth, indicating that as the growth time increases, the reaction system gradually stabilizes, and atoms or molecules can be deposited on the surface of the nanowires in a more orderly manner, which promotes the regular growth of the nanowires and reduces surface defects. The RL image shows that the SiCnw / EMR-2 only obtains a RL of -27.3dB in the 2.48mm and 11.77GHz bands. min and EAB at 0.69GHz.

[0066] Example 3

[0067] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0068] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0069] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 6 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-3);

[0070] Figure 3 The SEM images ((a) to (c)) and three-dimensional reflection loss (RL) images ((d)) of the SiCnw / EMR-3 at different magnifications show that the number of nanowires further increases after 6 hours of heat preservation, almost covering the entire observation area, forming a dense network structure. The diameter uniformity of the nanowires is further improved, and the overall morphology is more regular. In addition, it can be observed that some nanowires are agglomerated, which may be due to the interaction force between the nanowires, which increases with the increase in the number and length of the nanowires. As shown in the RL image, the SiCnw / EMR-3 only obtains a RL of -51.6dB in the 2.62mm and 11.8GHz bands. min and EAB at 2.04GHz.

[0071] Example 4

[0072] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0073] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0074] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1000°C, 6 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-4);

[0075] Figure 4 (a) is the three-dimensional reflection loss (RL) diagram of SiCnw / EMR-4, Figure 4 As shown in (a), the SiCnw / EMR-4 only achieves -14.3dB RL at 2.74mm and 10.951GHz. min and 1.4GHz EAB.

[0076] Example 5

[0077] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0078] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0079] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1100°C, 6 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-5);

[0080] Figure 4 (b) is the three-dimensional reflection loss (RL) diagram of SiCnw / EMR-5, Figure 4 As shown in (b), the SiCnw / EMR-5 only achieves -20.4dB RL at 4.6mm and 9.46GHz. min and EAB at 0.672GHz.

[0081] Example 6

[0082] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0083] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0084] The round cake-shaped green body was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1300°C, 6 hours, and a heating rate of 5°C / min). After cooling to room temperature at a cooling rate of 5°C / min, silicon carbide nanowires based on electrolytic manganese slag were obtained and sealed for storage (denoted as SiCnw / EMR-6);

[0085] Figure 4 (c) is the three-dimensional reflection loss (RL) diagram of SiCnw / EMR-6, Figure 4 As shown in (c), the SiCnw / EMR-6 only achieves -21.5dB RL at 2.89mm and 10.3GHz. min and EAB at 2.8GHz.

[0086] Comparative Example 1

[0087] 10 g of electrolytic manganese slag, 100 mL of alcohol and 100 mL of water were mixed to obtain a mixture;

[0088] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm.

[0089] The round cake-shaped blank was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200° C., 6 h, and a heating rate of 5° C. / min), and cooled to obtain an electrolytic manganese slag electromagnetic wave absorption composite material (EMR-1, the EMR-1 had a minimum reflection loss of -7.5 dB at 9.943 GHz at 3.14 mm and an effective absorption bandwidth of 0.048 GHz).

[0090] Comparative Example 2

[0091] 10 g of electrolytic manganese slag containing 10 wt% of bean dregs, 100 mL of alcohol, and 100 mL of water were mixed to obtain a mixture;

[0092] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm.

[0093] The round cake-shaped blank was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200° C., 6 h, and a heating rate of 5° C. / min), and cooled to obtain an electrolytic manganese slag electromagnetic wave absorption composite material (EMR-2, the EMR-2 had a minimum reflection loss of -12.3 dB at 9.04 GHz at 2.66 mm and an effective absorption bandwidth of 0.063 GHz).

[0094] Comparative Example 3

[0095] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0096] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0097] The round cake-shaped blank was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 7.5h, and a heating rate of 5°C / min), and cooled to obtain silicon carbide nanowires based on electrolytic manganese slag (denoted as SiCnw / EMR-7, the SiCnw / EMR-7 had a minimum reflection loss of -17.3 dB at 10.93 GHz at 2.78 mm, and an effective absorption bandwidth of 0.58 GHz).

[0098] Comparative Example 4

[0099] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag containing 10 wt % of bean dregs, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0100] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0101] The round cake-shaped blank was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 9h, and a heating rate of 5°C / min), and cooled to obtain silicon carbide nanowires based on electrolytic manganese slag (denoted as SiCnw / EMR-8, the SiCnw / EMR-8 had a minimum reflection loss of -13.1 dB at 11.812 GHz at 3.01 mm and an effective absorption bandwidth of 0.15 GHz).

[0102] Comparative Example 5

[0103] 8 g of glucose, 5 g of ethyl orthosilicate, 10 g of electrolytic manganese slag, 2 g of nickel nitrate, 100 mL of alcohol, and 100 mL of water were mixed under stirring (at a speed of 300 rpm) for 6 h to obtain a mixture;

[0104] The mixture was placed in an oven at 80° C. and dried for 12 h, and pressed at a pressure of 10 MPa for 2 min to obtain a round cake-shaped blank with a diameter of 30 mm;

[0105] The round cake-shaped blank was placed in a corundum boat and moved to a tube furnace for sintering (the sintering atmosphere was argon atmosphere, 1200°C, 6h, and a heating rate of 5°C / min), and cooled to obtain silicon carbide nanowires based on electrolytic manganese slag (denoted as SiCnw / EMR-9, the SiCnw / EMR-9 had a minimum reflection loss of -21.6 dB at 10.783 GHz at 3.64 mm and an effective absorption bandwidth of 0.57 GHz).

[0106] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation thereto. It should be noted that those skilled in the art may make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications shall also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing silicon carbide nanowires based on electrolytic manganese slag, characterized in that: The following steps are involved: mixing a carbon source, a silicon source, a pore former, electrolytic manganese slag, a nickel source and a dispersion medium to obtain a mixture; The mixture is sequentially pressed and sintered to obtain the silicon carbide nanowires based on electrolytic manganese slag; The sintering temperature is 1000-1300° C., and the heat preservation time is 3-6 hours.

2. The preparation method according to claim 1, wherein The mass ratio of the carbon source to the silicon source is (3-8): (5-10).

3. The preparation method according to claim 1 or 2, wherein The carbon source includes one or more of glucose, sucrose and starch; The silicon source includes one or more of silicon dioxide, tetraethyl orthosilicate and phenolic resin.

4. The preparation method according to claim 1 or 2, wherein The mass percentage of the pore-forming agent to the total mass of the pore-forming agent and the electrolytic manganese slag is 5 to 15%; The ratio of the mass of the carbon source to the total mass of the pore-forming agent and the electrolytic manganese slag is (3-8): (10-50).

5. The preparation method according to claim 4, wherein The pore-forming agent includes one or more of bean dregs, rice husks, corn cobs and coffee grounds.

6. The preparation method according to claim 1 or 5, characterized in that: The mass ratio of the carbon source to the nickel source is (3-8): (2-10); The nickel source includes one or more of nickel nitrate, nickel sulfate and nickel chloride.

7. The preparation method according to claim 1, wherein Before the compression molding, the process also includes drying; The drying temperature is 60-100°C and the drying time is 6-12 hours; The compression molding pressure is 5-20 MPa, and the holding time is 1-5 minutes.

8. The preparation method according to claim 1, wherein The sintering is carried out in a protective atmosphere; The heating rate to the sintering temperature is 1-10°C / min.

9. Silicon carbide nanowires based on electrolytic manganese slag prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the silicon carbide nanowires based on electrolytic manganese slag according to claim 9 in the field of electromagnetic wave absorption.